Characterization of bioactive colored materials produced from bacterial cellulose and bacterial pigments - Amorim, Lúcia F. A. (2022)
A Bacterial Cellulose (BC) film was developed and characterized as a potential functional bioactive material. BC films, obtained from a microbial consortium of bacteria and yeast species, were functionalized with the bacterial pigment prodigiosin, produced by Serratia plymuthica, and flexirubin-type pigment, from Chryseobacterium shigense, which exhibit a wide range of biological properties. BC was successfully functionalized at 15% over the weight of the fiber at 40 °C during 60 min, and a color strength of 1.00 ± 0.01 was obtained for BC_prodigiosin and 0.38 ± 0.02 for BC_flexirubin-type pigment. Moreover, the BC films showed moderate hydrophilic character following alkaline treatment, which was maintained after both pigments were incorporated. The porosity and mechanical performance of the functionalized BC samples also remained unaffected. Furthermore, the BC samples functionalized with prodigiosin presented antibacterial activity and were able to inhibit the growth of pathogenic bacteria Staphylococcus aureus and Pseudomonas aeruginosa, with inhibition rates of 97.89 ± 0.60% and 85.12 ± 0.17%, respectively, while BC samples functionalized with flexirubin-type pigment exhibited the highest antioxidant activity, at 38.96 ± 0.49%. This research provides an eco-friendly approach to grant BC film-based material with color and advantageous bioactive properties, which can find application in several fields, especially for medical purposes.